WAYS OF FORMATION OF READYNESS OF FOREIGN LANGUAGE TEACHERS FOR PERSONALITY-ORIENTED LEARNING OF SENIOR STUDENTS (Pedagogy of Higher and Secondary Education, 2009)
In the article the essence and contents of the notion of readiness of future teachers of foreign languages for personality-oriented teaching high-school  pupils is revealed. On the basis of analysis of the literary sources the above mentioned phenomenon is defined and the ways of forming this complex unity of personality in students of the department of foreign languages are noted.